Sistem Pendukung Keputusan Penentuan Pemberian Insentif Pegawai THL Menggunakan Metode Promethee Pada Kantor Walikota Pematangsiantar - Sepridho, Jaka; Damanik, Irfan Sudahri; Okprana, Harly (STMIK Budi Darma, 2021)
Pematangsiantar Mayor Office is an institution that is used and functions to serve and protect the community. This paper proposes a decision support system research using the Promethee method. Promethee is one of several methods of determining the order or priority in multi-criteria analysis. This writing uses the Promethee method as a step in determining the provision of incentives for freelance daily staff at the Pematangsiantar Mayor's Office. In this study the authors took 10 alternatives with 5 assessment criteria including absenteeism, achievement, behavior, long history of work and teamwork. With the highest result obtained by alternative 9 on behalf of Triono with a value of 0.422 and the lowest result obtained by alternative 6 on behalf of Soraya with a value of -0.211.